The topology, structure and PE interaction of LITAF underpin a Charcot-Marie-Tooth disease type 1C. Issue 1 (December 2016) - Ho, Anita; Wagstaff, Jane; Manna, Paul; Wartosch, Lena; Qamar, Seema; Garman, Elspeth; Freund, Stefan; Roberts, Rhys
Abstract Background Mutations in Lipopolysaccharide-induced tumour necrosis factor-α factor (LITAF ) cause the autosomal dominant inherited peripheral neuropathy, Charcot-Marie-Tooth disease type 1C (CMT1C).LITAF encodes a 17 kDa protein containing an N-terminal proline-rich region followed by an evolutionarily-conserved C-terminal 'LITAF domain', which contains all reported CMT1C-associated pathogenic mutations. Results Here, we report the first structural characterisation of LITAF using biochemical, cell biological, biophysical and NMR spectroscopic approaches. Our structural model demonstrates that LITAF is a monotopic zinc-binding membrane protein that embeds into intracellular membranes via a predicted hydrophobic, in-plane, helical anchor located within the LITAF domain. We show that specific residues within the LITAF domain interact with phosphoethanolamine (PE) head groups, and that the introduction of the V144M CMT1C-associated pathogenic mutation leads to protein aggregation in the presence of PE. Conclusions In addition to the structural characterisation of LITAF, these data lead us to propose that an aberrant LITAF-PE interaction on the surface of intracellular membranes contributes to the molecular pathogenesis that underlies this currently incurable disease.